Determinants of urban worker earnings in Ghana and Tanzania: The role of education - Priscilla Twumasi Baffour (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
The paper examines the role of education in earnings determination by using all three rounds of the Urban Worker Surveys of Tanzania and Ghana for 2004-2006. We investigate and compare heterogeneity in earnings determinants among self-employed (informal), private and public sector workers. We examine the role education, individual and household characteristics play in facilitating entry into employment sectors in addition to analysing the pattern of returns to education along the earnings distribution. After addressing endogeneity and selectivity biases associated with estimating earnings equations, we find that education plays an important role in promoting access to formal sector jobs, particularly employment in the public sector, but has no direct impact on earnings within the sector in both countries. Results from quantile regressions indicate primary and secondary levels of education are inequality-reducing among workers in Tanzania but this is not the case in Ghana. Tertiary education on the other hand is found to widen earnings inequality in both Tanzania and Ghana.
Keywords: 330; Education; Earnings; Employment Sector; Tanzania; Ghana